PERILAKU SINTAKSIS ADJEKTIVA BAHASA MELAYU JAMBI DESA TUNAS BARU KECAMATAN SEKERNAN KABUPATEN MUARO JAMBI (KAJIAN MORFOSINTAKSIS) - Supriyati Supriyati; Ainun Mardiah (Universitas Batanghari, 2021)
This study aims to describe and document the syntactic behavior of adjectives from aspects of attributed functions, predicative functions, and adverbial functions of Jambi Malay language in Desa Tunas Baru Kecamatan Sekernan Kabupaten Muaro Jambi The study uses qualitative descriptive method, the data collection techniques used are observation and structured interviews. In this study, the data in adjective syntax behavior was taken from 6 informants, with the provision of samples taken based on the direction of the wind that is a native speaker of Jambi Malay in Desa Tunas Baru Kecamatan Sekernan Kabupaten Muaro Jambi. The data is analyzed by using the distributional analysis method. This study shows the syntactic behavior of adjectives in Jambi Malay Desa Tunas Baru Kecamatan Sekernan Kabupaten Muaro Jambi includes the attribute function of an adjective, predicative function adjective and adverbial function or adjective information. The adjective syntax behavior of the attributed function is found in the sentence dudoklah kautu di kursi rogot tu, jangan di bawah dudok e, which means (let's sit on the old chair, do not sit down). The syntactic behavior of adjectives from the aspect of predicative function is found in the sentence of orang tu kiniko bangat, sian nengok e, which means (the person is now sick, pity to see it). Then the adjective syntactic behavior of the aspect of adverbial function or description is found in the sentence demi nyekolahi anak e Ayah kerjo dengan soho-soho, which means (For the sake of sending his son to school, his father works earnestly). Keywords: Jambi Malay language morphosyntax, adjective function